Hunting time - Deaver, Jeffery (G.P. Putnam's Sons, 2022)
Allison Parker is on the run with her teenage daughter, Hannah, and Colter Shaw has been hired by her eccentric boss, entrepreneur Marty Harmon, to find and protect her. Though he?s an expert at tracking missing persons?even those who don?t wish to be found?Shaw has met his match in Allison, who brings all her skills as a brilliant engineer designing revolutionary technology to the game of evading detection. The reason for Allison?s panicked flight is soon apparent. She?s being stalked by her ex-husband, Jon Merritt. Newly released from prison and fueled by blinding rage, Jon is a man whose former profession as a police detective makes him uniquely suited for the hunt. And he?s not alone. Two hitmen are also hot on her heels?an eerie pair of thugs who take delight not only in murder but in the sport of devising clever ways to make bodies disappear forever. Even if Shaw manages to catch up with Allison and her daughter, his troubles will just be beginning.